Comparison of sealing ability of lateral and vertical techniques in two different post space preparations - Shiva Sadeghi, Shiva Sadeghi; Kangarloo, Ali (Iranian Endodontic Journal, 2008)
Introduction: The purpose of this study was to compare the apical sealing ability of lateral and vertical compaction techniques following immediate and delayed post space preparation. Materials and Methods: Seventy-four distal and palatal roots of human extracted molars were instrumented and randomly divided into 4 experimental groups (n=15), two experimental control groups (n=5), and two positive and negative leakage controls (n=2). Canals were filled by lateral (groups 1 and 2) and vertical (groups 3 and 4) compaction techniques using Tubliseal sealer. Post space was prepared immediately after obturation in group 1 and after seven days in groups 2 and 4 using a # 3 Peeso drill. In group 3, post space was prepared immediately during down-packing phase. The teeth were kept in 2% methylen blue dye for seven days. The roots were sectioned buccolingually and the mean score of dye penetration was measured. Data was analyzed with T-test and one way ANOVA. Results: There was significant difference in dye penetration between delayed and control-lateral compaction groups (p=0.009). There was also a significant difference in dye penetration between immediate and delayed lateral compaction groups (p=0.044). Conclusion: Less apical leakage in the cold lateral condensation and immediate post space preparation group was observed.